Flohria Sharp - a Relictual Genus of the Subtribe Philonthina From the Americas (Coleoptera: Staphylinidae: Staphylininae) - Chani Posse, Mariana Raquel (2015)
Flohria subcoerulea (LeConte), a relictual genus and species of the subtribe Philonthina (tribe Staphylinini) from the Americas, is redescribed and illustrated, its distribution documented, and lectotypes designated. The phylogenetic position of the genus within Philonthina, as well as its potential age and origin, is discussed.